A study to investigate the elements that affect students’ willingness to use ICT in the learning and teaching process in higher education in Uttar Pradesh (Revista de Investigaciones Universidad del Quindío, 2022)
Greater emphasis is being placed on higher education in India because of developments in Information Communication Technology (ICT). The Internet of Things (IoT) is the driving factor behind the effective delivery of high-quality education in higher education. Over the last two decades, progress in ICT has been integrated into universities worldwide. There is a growing need for highly qualified and capable professionals in today’s globalized world. Even though the Indian government sponsors students from basic school through higher education, much more must be done to transform the country into a technologically literate and educated society. Access to high-quality education has emerged as a critical component in the promotion of economic development and growth worldwide. The contribution of online learning courses, as well as distance learning courses, is growing as a method of extending access to quality education and reaching the country’s most remote locations. In terms of available communication and information technologies, India is now facing a substantial shift in ICT. Furthermore, it is addressing the demands of people who want to complete their studies for the rest of their life at a low cost. Despite its obvious benefits and possibilities, the use of Information Communication Technology (ICT) in education is fraught with uncertainties and challenges.
Keywords: ICT; Higher education; e-learning; Communication; Digital India; Learning; Teaching